Phineas and Ferb. Mission marvel [videorecording (DVD)]. - Tisdale, Ashley, 1985-; Rhea, Caroline, 1964-; Stoner, Alyson, 1993- (Walt Disney Studios Home Entertainment, 2013)
It's thwarted-business-as-usual for Dr. Doofenshmirtz, until a blast from his power-drain-inator ricochets off of Phineas and Ferb's space station, hitting Spider-Man, Iron Man, the Hulk, and Thor. Now the kids must restore the super heroes' lost powers before a group of dastardly super-villains destroy the planet! Fortunately, Nick Fury and S.H.I.E.L.D. are also on the case, together with O.W.C.A.'s top agent, Perry the Platypus.